2018
DOI: 10.18203/2320-1770.ijrcog20184922
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein as a screening test for gestational diabetes mellitus in first-trimester of pregnancy: a prospective cohort study

Abstract: Background: The current study aims to determine if increased inflammation identified by increased C-reactive protein (CRP) level is associated with the subsequent development of gestational diabetes mellitus (GDM).Methods: A prospective cohort study conducted at a tertiary University Hospital included 496 booking for their antenatal care visit between 10-12 weeks of gestation. They were tested for presence of CRP in blood. All women without a history of antenatal type 1 or type 2 diabetes undergo routine GDM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…In a current study out of ninety-three patients with raised CRP, 8(8.6%) developed GDM (p<0.00001) showing that high C-reactive protein can result in GDM. This is inconsistency with previous research studies 13,14 . Increased levels of CRP in the blood can lead to hyperglycaemia by influencing insulin resistance 15 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a current study out of ninety-three patients with raised CRP, 8(8.6%) developed GDM (p<0.00001) showing that high C-reactive protein can result in GDM. This is inconsistency with previous research studies 13,14 . Increased levels of CRP in the blood can lead to hyperglycaemia by influencing insulin resistance 15 .…”
Section: Discussioncontrasting
confidence: 99%
“…A research study by Cunningham et al showed that the sensitivity and specificity of GCT in GDM screening varies with glucose thresholds such as 80% and 82-86% with 140mg/dl while 90% and 75-80%when kept at 130mg/dl 20 . Whereas Farghaly et al reported that CRP has a sensitivity and specificity of 86.49% and 98.47% respectively in detecting GDM 13 . The current study showed 100% sensitivity and 48.17% specificity of CRP in detecting GDM thus making it a good screening test for GDM owing to the very high sensitivity and simplicity of the test.…”
Section: Discussionmentioning
confidence: 96%
“…Relatively recently, serum levels of C-reactive protein (CRP) as well as glycated hemoglobin (HbA1c) and random blood sugar (RBS) are used as screening tools for GDM in the first trimester. CRP concentrations of about 6 mg/L or higher in undiluted serum samples are considered positive for GDM [149]. According to the International Association of the Diabetes and Pregnancy Study Group (IADPSG), the cutoff level of HbA1c is 6.5 % and RBS is 11.1 mmol (200mg/dL) [150].…”
Section: Gdm Testing Efficacy and Cost-effectivenessmentioning
confidence: 99%